The Clinical Significance of Shock Index and GFR in the Differential Diagnosis of Perforated Appendicitis - Ali Duran; Ferhat Çay (Journal of Contemporary Medicine, 2022)
Aim: The aim of the study is to investigate whether the shock index (SI) and glomerular filtration rate (GFR) have significance in differentiating acute appendicitis from complicated perforated acute appendicitis. Materials-Methods: Patients were searched retrospectively on the hospital database. Age, gender, C-reactive protein (CRP), leukocyte (WBC), total bilirubin (T.BIL), urea, creatinine, pulse (NBZ), and arterial blood pressure (TA) values of the patients were searched retrospectively on the hospital database and a database was created by using these patient variables. GFR and SI were calculated by using these data. The surgical notes about patients were reviewed retrospectively, and they were divided into two groups, namely perforated appendicitis and non-perforated appendicitis. The data were analyzed to investigate whether GFR and SI were effective in predicting perforation. Results: It was observed that NB/TA value had more frequent pathological findings in patients with perforated appendicitis (p lt;0.001). It was found that age (p=0.001), CRP (p lt;0.001), WBC (p lt;0.001), T. BIL (p=0.002), NB (p=0.017), and NB/TA (p lt;0.001) values of the patients in the perforated appendicitis group were higher than those of the patients in the normal appendicitis group, while GFR (p lt;0.001) and TA (p lt;0.001) values were lower (p lt;0.05). Conclusion: It is thought that SI and GFR may be a prognostic parameter for showing both perforation and the associated increased mortality rate.